2023
DOI: 10.18097/pbmc20236902083
|View full text |Cite
|
Sign up to set email alerts
|

Features of oxidative stress in alcoholism

Abstract: The review considers molecular mechanisms underlying formation and development of oxidative stress (OS) in patients with alcohol dependence. The major attention is paid to the effects of ethanol and its metabolite acetaldehyde associated with additional sources of generation of reactive oxygen species (ROS) in response to exogenous ethanol. The own results of studies of the in vitro effect of ethanol and acetaldehyde on the concentration of peripheral OS markers — products of oxidative modification of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…There are changes in these parameters and the activity of antioxidant enzymes (SOD and catalase) in patients with AUD. Studies indicate that, at a particular stage of the disease, oxidative stress could play a protective rather than pathogenic role in the body [ 129 ]. There are also several genes related to DTs [ 130 ].…”
Section: Future Directionmentioning
confidence: 99%
“…There are changes in these parameters and the activity of antioxidant enzymes (SOD and catalase) in patients with AUD. Studies indicate that, at a particular stage of the disease, oxidative stress could play a protective rather than pathogenic role in the body [ 129 ]. There are also several genes related to DTs [ 130 ].…”
Section: Future Directionmentioning
confidence: 99%
“…Studies have shown that alcohol can interfere with the function of the hypothalamus-pituitary-gonadal (HPG) axis and reduce the production of gonadotropin releasing hormone (GnRH), luteinizing hormone, and follicle-stimulating hormone, resulting in the impairment of the activity of Leydig and Sertoli testicular cells, which play a crucial role in testosterone production and sperm maturation respectively [7]. Moreover, alcohol metabolism generates an excess of reactive oxygen species (ROS), thereby causing a discrepancy in the oxi-dative stress status of the organism [8,9]. This mechanism is considered the main way by which alcohol induces ultrastructural changes in the male reproductive system.…”
Section: Introductionmentioning
confidence: 99%